Knema namkadingensis, a new species of Myristicaceae from Central Laos - Phengmala, Kajonesuk; Souladeth, Phetlasy; Kongxaisavath, Deuanta; Sengthong, Anousone; Souvannakhoummane, Keooudone; Dang, Van-Son; Yamamoto, Takenori; Tagane, Shuichiro (Phytotaxa, 2025)
A new species of Knema (Myristicaceae), K. namkadingensis is described from the Nam Kading National Protected Area, Bolikhamxai Province in central Laos. It is found growing in dry evergreen forest. The species can be distinguished from other species of Knema in Laos and surrounding countries by its small habit of up to 3 m tall, small leaves shorter than 10 cm long, small male flowers measuring 2.5–3 mm in diameter, and obovoid-ellipsoid fruits with acute apices.